2019
DOI: 10.1002/jcb.29377
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an in vitro model of β‐thalassemia using the CRISPR/Cas9 genome editing system

Abstract: β‐Thalassemia is a common monogenic disease characterized by defective β‐globin chains synthesis. In vitro β‐thalassemia‐related research on increasing β‐like globin genes or identification of factors reducing the severity of the disease, has been performed on mouse erythroleukaemia or K562 cell lines. The aim of this study was the production of an in vitro model of β‐thalassemia using the highly efficient CRISPR‐Cas9 system. Embryonic stem (ES) cells were nucleofected with guide RNA (gRNA)‐Cas9 expression vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…With exercise, Hbb-b1 expression was upregulated in SOL and downregulated in GAS ( Table 3 ). Hbb-b1 is linked to the formation of hemoglobin, and the mutation of Hbb-b1 is associated with abnormal oxygen transportation [ 47 ]. As Hbb-b1 is involved in oxygen transportation and exhibits the most prominent differences between SOL and GAS, further studies should be conducted to clarify the interaction between this protein and muscle fiber type.…”
Section: Discussionmentioning
confidence: 99%
“…With exercise, Hbb-b1 expression was upregulated in SOL and downregulated in GAS ( Table 3 ). Hbb-b1 is linked to the formation of hemoglobin, and the mutation of Hbb-b1 is associated with abnormal oxygen transportation [ 47 ]. As Hbb-b1 is involved in oxygen transportation and exhibits the most prominent differences between SOL and GAS, further studies should be conducted to clarify the interaction between this protein and muscle fiber type.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an animal model of β‐thalassemia similar to the SCD animal model, a study used CRISPR–Cas9 to knock down the HBB‐B1 gene in ES cells to construct a mouse model of β‐thalassemia (Hbbth1/th1) in vitro, which was used to explore the molecular basis and therapeutic options for β‐thalassemia. 172 β 654 ‐thalassemia mice containing the βIVS‐2‐654 splice mutation in the human gene mimic the symptoms of moderate to severe β‐thalassemia, and studies were conducted to construct β 654 ‐ER mice capable of correctly splicing the β‐thalassemia by gene editing the mutation and splice site using CRISPR/Cas9. 173 The therapeutic role of HSC transplantation in β 654 ‐ER mice was further explored, and the results showed that HSC from gene‐edited mice was able to achieve hematopoietic reconstruction and long‐term hematopoiesis in vivo, and completely restored the phenotype of β‐thalassemia, and the construction of the mouse model provided a reference for the clinical application of gene‐edited HSC.…”
Section: Animal Models Used In Preclinical Studies On Human Diseasesmentioning
confidence: 99%
“…The CRISPR/Cas9 technology is now being utilized for versatile applications such as precise interrogation of basic biological functions (Hilton and Gersbach, 2015), development of biotechnology products (e.g., vaccines) (Okoli et al, 2018;Chang et al, 2019) and treatment of diseases (Morishige et al, 2019;Ajami et al, 2020). This technology can therefore be harnessed for ASFV functional genetics to elucidate the role of specific genes in virus replication processes, virus-host interactions, or virus virulence, and more importantly for accelerating vaccine development for ASF.…”
Section: Introductionmentioning
confidence: 99%